NEUROLOGICAL OUTCOME AFTER CORONARY ARTERY BYPASS SURGERY - Khan, Ammar Hameed; Khilji, Shahbaz Ahmad (Journal of Ayub Medical College Abbottabad, 2004)
Background: Neurological dysfunction is a common complication after cardiac surgery. Despite significant advances in cardiopulmonary bypass (CPB) technology, surgical techniques and anaesthetic management, central nervous system complications occur in a large number of patients undergoing surgery requiring CPB. The objective of this study was to determine neurocognitive status of the patients undergoing coronary artery bypass grafting (CABG) and to find any causative or associated factor. Methods: We evaluated 1000 consecutive patients undergoing primary isolated coronary artery bypass grafting (CABG) at a tertiary care cardiac institute from July 2000 to December 2001 to determine the neurological outcome after CABG and risk factors involved. The demographic and perioperative data were analyzed by X2 analysis. Results: A history of diabetes, hypertension, increased age, preoperative neurological event, aortic atheromatous / calcific disease, bilateral carotid artery disease, intermittent aortic cross clamping and evidence of mural thrombi are all co-related with increased risk of neurological damage after CABG. When analyzed in a stepwise logistic regression model, diabetes mellitus, aortic disease, increased age and mural thrombi carried a higher probability that the patient would have a postoperative neurological deficit. Conclusions: We conclude that although these factors are individually involved in the adverse neurological outcome after CABG but the combination of these factors greatly increases the risk of postoperative neurological consequences and only few of them are avoidable. Key words: CABG, CPB, complications, neurological, risk factors, PIC.